2001
DOI: 10.1007/s002280100347
|View full text |Cite
|
Sign up to set email alerts
|

Is cognitive impairment a risk factor for poor compliance among Japanese elderly in the community?

Abstract: We found that cognitive impairment was one of the predictors for poor compliance among the elderly who are functionally independent in the community. Intentional noncompliance was the strongest predictor for poor compliance, which was influenced by the relationship between patient and physician. Physicians should establish good communication with their elderly patients and provide some support to compensate for cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
3
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 23 publications
4
90
3
8
Order By: Relevance
“…Patients who received INR results from the clinic had better compliance. These results support past studies that showed low compliance in patients who had lack of belief in the benefit of the treatment (Okuno et al, 2001;Lacro et al, 2002), or a lack of insight into the illness (Lacro et al, 2002). In contrast, greater understanding of why medication was prescribed and anticipated side effects was found as a predictor for enhanced compliance (Bushnell et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients who received INR results from the clinic had better compliance. These results support past studies that showed low compliance in patients who had lack of belief in the benefit of the treatment (Okuno et al, 2001;Lacro et al, 2002), or a lack of insight into the illness (Lacro et al, 2002). In contrast, greater understanding of why medication was prescribed and anticipated side effects was found as a predictor for enhanced compliance (Bushnell et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…In general, predictors for low compliance to therapy include disease-related factors, such as treatment of chronic disease (Haynes et al, 2002;Jackevicius et al, 2002), treatment of asymptomatic disease (Sewitch et al, 2003), side effects of medication (van Servellen et al, 2002), complexity of treatment (Ammassari et al, 2002); psychological factors (Ammassari et al, 2002;Stilley et al, 2004), and cognitive impairment (Okuno et al, 2001;Stilley et al, 2004). Another group of factors that can affect drug compliance are related to contact with medical staff, such as poor physician-patient relationship (Urquhart, 2002;van Servellen et al, 2002), inadequate follow-up or discharge planning, and missed appointments (Lacro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hanlon et al 5 (1996) expressed concern that lower consumption of medications among elderly people with cognitive impairment might constitute underuse of medications, because doctors had failed to prescribe adequate drug therapy, infl uenced by knowledge of their patients' cognitive status. Knowing that elderly people with abnormal cognitive function are more likely not to comply with a therapeutic regimen, 19 doctors perhaps become more parsimonious in their prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that participation has been better when there is a positive relationship between patient and care provider [22]. This is particularly important in the current study in which interviewers were in frequent contact with the participants and were able to answer any of their questions regarding participation or try to find ways to help participants improve their cooperation (for example, place a note on the apartment door reminding them to take the equipment).…”
Section: Discussionmentioning
confidence: 94%